Efektivitas Inovasi Pelayanan AYO SKAK terhadap Kepemilikan Akta Kematian di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Wonogiri: (Studi kasus pada Dinas Kependudukan dan Pencatatan Sipil Kabputaen Wonogiri ) - Hartanto, Sri; Pramono, Joko (Solidaritas, 2024)
The innovative service program implemented by the Disdukcapil (Departmentof Population and Civil Registration) of Wonogiri Regency, called “AYOSKAK,” aims to simplify the process of creating death certificates, making iteasier for the public to manage their documentation and reducing queues atDisdukcapil. Although this innovative program has been running, there are stillchallenges, such as a lack of public understanding regarding the application’suse and frequent errors in the application.This research aims to assess, describe, and analyze the effectiveness of the“AYO SKAK” service innovation at Disdukcapil Wonogiri Regency. The studyemploys a descriptive research method with qualitative data analysis. Datacollection techniques include observation, interviews, and documentationrelated to the “AYO SKAK” service innovation. The collected data are thenanalyzed qualitatively, considering all gathered information and supported byinterview results, referencing the theory proposed by Budiani (2007) thateffectiveness can be measured through the accuracy of program targets,program socialization, program objectives, and program monitoring.The research findings indicate that the implementation of the “AYO SKAK”service innovation has been effective and has positively impacted the increase inthe ownership of death certificates in Wonogiri Regency. This can be observedthrough the four indicators mentioned. The target accuracy indicator is onpoint, the program socialization indicator is effective and comprehensive, theprogram objectives align with the goal of facilitating public access to deathcertificate processing and increasing ownership coverage in Wonogiri, and theprogram monitoring indicator shows that regular monitoring and evaluationhave been conducted. Nonetheless, there is a need to optimize the system tomake it easier for the public to access the application and reduce the occurrenceof errorsKeywords: Effectiveness, innovation, eath certificate.